State Financing of Political Parties as a Chance for Healing the Party System: Polish Experience and Ukrainian Realities - Balashova, Oksana; Sydoruk, Tetiana (Politologija, 2018)
[full article, abstract in English]The process of state financing of the political parties in Poland and Ukraine has been analyzed in this article. The authors have studied and compared the theoretical foundations of the Polish and Ukrainian legislation in the sphere of state financing of the functioning of the political parties. By comparing the experience of state financing of political parties in Poland and Ukraine, the authors have distinguished a number of direct and indirect positive consequences in the party system of Poland. It has been determined that in Ukraine, in turn, considering the lack of legal and public sources for financing political parties, political and economic spheres are closely interdependent, which significantly impedes the qualitative consolidation of the party system in general. The authors have concluded that the positive effect of state financing of political parties is primarily reflected in an increase in the level of openness in how the political parties function, the transparency of the parties’ financial activities, the independence of the party system and the political transparency of civil society.
Keywords: none